2017
DOI: 10.2134/cftm2016.12.0077
|View full text |Cite
|
Sign up to set email alerts
|

Forage Mass, Nutritive Value, and In situ Degradation of Sorghum Silage Treated with Fibrolytic Enzymes

Abstract: Core Ideas Xylanase and cellulase treatment of sorghum silage did not affect sorghum silage nutritive value. The brown midrib trait and harvest timing have more influence on silage quality than fibrolytic enzymes. Sorghum [Sorghum bicolor (L.) Moench.] and sorghum‐sudangrass (S. bicolor × S. bicolor drummondii) silage utilization in cattle diets has increased in recent years. The objectives of this study were to compare the forage mass and nutritive value of photoperiod‐sensitive (PS) sorghum and hybrid sist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In review, Oliveira et al (7) concluded that the divergences in results may be related, among other factors, to the different variations of the inoculant used, and also of the diet. Just like McCuistion et al (25) , with the addition of cellulase containing inoculant, it was expected that the fiber would be better utilized, which was not observed since it is a food with low contents of this component. In general, nutrient and dry matter digestibility of high moisture triticale silage were not affected (P>0.05; Table 5) by the addition of no additives, however, all diets showed dry matter digestibility compatible with high moisture corn and sorghum silage, which are the reference foods for this variable (26,27) .…”
Section: Figure 1: Value Of Ph During the Aerobic Stability Testmentioning
confidence: 97%
“…In review, Oliveira et al (7) concluded that the divergences in results may be related, among other factors, to the different variations of the inoculant used, and also of the diet. Just like McCuistion et al (25) , with the addition of cellulase containing inoculant, it was expected that the fiber would be better utilized, which was not observed since it is a food with low contents of this component. In general, nutrient and dry matter digestibility of high moisture triticale silage were not affected (P>0.05; Table 5) by the addition of no additives, however, all diets showed dry matter digestibility compatible with high moisture corn and sorghum silage, which are the reference foods for this variable (26,27) .…”
Section: Figure 1: Value Of Ph During the Aerobic Stability Testmentioning
confidence: 97%
“…With modeling, IV and IS techniques can bring together measures of fiber, which are laboratory measures, to in vivo apparent digestibility and intake, which are animal-influenced measures, as a proxy to expensive and time- and labor-consuming feeding trials, which require much larger amounts of feedstuffs and more animal experimental units. Ranking of IV or IS results can help determine forages in breeding programs that are most suitable for advancement ( Foster et al, 2007 ), impact of genetic traits on potential animal performance ( McCuistion et al, 2017 ), the ideal maturity stage for harvest ( Foster et al, 2012 ), harvested forage preservation method ( Foster et al, 2011 , 2012 ), harvested forage preservation aids such as enzyme or microbial applications before ensiling ( Thomas et al, 2013 , 2014 ; McCuistion et al, 2017 ; Foster et al, 2019 ), alternative uses of row crop residues ( Foster et al, 2012 , 2019 ), supplementation regimes ( Smith et al, 2017 ), and among many other applications.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in NDF concentration of silage inoculated with a mixture of homo‐ and heterofermentative lactic acid bacteria is attributed to bacterial strains that provide ferulic acid esterase activity, resulting in greater hemicellulose disappearance (Morais et al, 2017). The effects of sorghum silage pretreatment are not consistent; there was no effect of either fibrolytic enzyme or lactic acid bacteria inoculant pretreatment when sorghum had lignin concentrations <30 g kg −1 (McCuistion et al, 2017). The impact of pretreatment with fibrolytic enzymes or heterofermentative lactic acid bacterial inoculants on sorghum silage without grain is unknown.…”
mentioning
confidence: 99%